Equipment selection for strength training: Free weights or machines - Some practical aspects for coaches - Stone, M.; Plisk, S. (coachesinfo.com)
An area of strength training, which has been somewhat controversial, concerns the mode of exercise, i.e. free weights or machines. Often fitness instructors and particularly strength and conditioning coaches are bombarded with advertisements that expound upon the virtues of various types of resistance training equipment. Making appropriate selections of resistance training equipment can be paramount in producing maximum performance gains. The purpose of this review is to briefly examine the role of different modes of strength training in strength training programs. Summary: While a number of factors would seem to indicate that free weights can produce superior results, the major factor appears to deal with mechanical specificity. From the standpoint that specificity of exercise and training can result in superior adaptations free weight training should produce a greater carry-over to other performance aspects of sport.